Upaya Meningkatkan Minat Belajar Kimia Peserta Didik Melalui Kemampuan Kreatif Dan Inovatif Pendidik - Ulfa Lutfianasari; Devy Lestari (Journal on Education, 2024)
The Merdeka Curriculum focuses on basic material, character development and competency. The independent curriculum provides the opportunity for classes XI and XII to choose subjects according to their preferred interests. Based on interviews and observations conducted at SMAN 14 Semarang, it is known that chemistry is the least popular subject because it is the first subject with the lowest number of voters. Therefore, efforts that can increase student interest need to be made. The aim of this research is to conduct an analysis of the efforts made to increase students' interest in learning chemistry. The method used in this research is descriptive qualitative. The research results show that innovative and creative teachers have an impact on students' interest in learning chemistry. innovative and creative teachers can use various creative ideas in learning, such as choosing learning approaches, learning media, and creating a pleasant classroom atmosphere.